Entropy and cycles - Mills, Bartow, author; Yust, David E., advisor; Sullivan, Patrice M., advisor; Lehene, Marius, committee member; Steensen, Sasha, committee member (Colorado State University. Libraries, 2010)
This body of works subject and focus point is the cyclical nature of matter and the forces therein. There have been explorations of this concept on all fronts including metaphysical philosophy, science, and art. It is the recurring realization of matter as a cyclical form being driven by unseen forces that leads me to believe the subject is of utmost importance. Through the use of a specific set of marks, surfaces, symbols, and imagery I am attempting to conjure this realization and come to a better understanding of the concept, and to ultimately echo a similar response in an audience.
Department Head: Gary Wayne Voss.